e-Vital: A Wrist-Worn Wearable Sensor Device for Measuring Vital Parameters - Özcan, Özgür; Çınar, İpek; AKBULUT, FATMA PATLAR (My University, 2019)
In today’s world, connected wearable sensors became a delicate part of the imperative daily analysis and assessment to identify the urgency of the state of health. Recent advances in sensor designs and analysis techniques enable us to uniquely distinguish noninvasive wearable sensor technology with an exclusive integration to the body surfaces. In this regard, we have developed a low-cost wrist-worn wearable device called E-Vital that can monitor health conditions closely so that patient follow-up can access information directly and in a practical way. We aimed to design the system as a comprehensive and compact monitoring scheme by measuring physiological health parameters in long-term usage. In addition to the measurement of physiological signals such as an electrocardiogram (ECG), Galvanic Skin Response (GSR) and body temperature, it is possible to instantly display and store this health data with the E-Vital mobile application. Bluetooth technology is used to provide instant wireless data communication between the sensor device and the mobile application. Additionally, an SD card module attached to the sensor to prevent data loss against possible connection problems as a local buffer. The measurement performance of the proposed sensor device for capturing the electrophysiological signals, such as an ECG is compared with ECG obtained by a conventional gold standard data. The results indicate that the wearable sensor has an acceptable signal-to-noise ratio (SNR). Both the sensor device and mobile system have successfully been in terms of signal quality, continuous data transportation, and data storing performance during on-body trials.
Keywords: e-health; Healthcare; Biosensor; Telemetry; Health Monitoring; Wearable Systems; e Hağlık; Sağlık Hizmeti; Biyoalgılayıcı; Telemetri; Sağlık Takibi; Giyilebilir Sistemler